Association of Bone Loss with the Upregulation of Survival-Related Genes and Concomitant Downregulation of Mammalian Target of Rapamycin and Osteoblast Differentiation-Related Genes in the Peripheral Blood of Late Postmenopausal Osteoporotic Women - Elena V. Tchetina; Karina A. Maslova; Mikhail Y. Krylov; Valery A. Myakotkin (Journal of Osteoporosis)
We aimed to identify bone related markers in the peripheral blood of osteoporotic (OP) patients that pointed toward molecular mechanisms underlying late postmenopausal bone loss. Whole blood from 22 late postmenopausal OP patients and 26 healthy subjects was examined. Bone mineral density (BMD) was measured by DXA. Protein levels of p70-S6K, p21, MMP-9, TGFβ1, and caspase-3 were quantified by ELISA. Gene expression was measured using real-time RT-PCR. OP registered by low BMD indices in late postmenopausal patients was associated with a significant upregulation of autophagy protein ULK1, cyclin-dependent kinase inhibitor p21, and metalloproteinase MMP-9 gene expression in the blood compared to the healthy controls and in a significant downregulation of mTOR (mammalian target of rapamycin), RUNX2, and ALPL gene expression, while expression of cathepsin K, caspase-3, transforming growth factor (TGF)β1, interleukin- (IL-) 1β, and tumor necrosis factor α (TNFα) was not significantly affected. We also observed a positive correlation between TGFβ1 and RUNX2 expression and BMD at femoral sites in these patients. Therefore, bone loss in late postmenopausal OP patients is associated with a significant upregulation of survival-related genes (ULK1 and p21) and MMP-9, as well as the downregulation of mTOR and osteoblast differentiation-related genes (RUNX2 and ALPL) in the peripheral blood compared to the healthy controls.